PENGARUH STRATEGI PEMBELAJARAN DAN KEMANDIRIAN TERHADAP HASIL BELAJAR BAHASA INGGRIS SISWA SMPS GALIH AGUNG DAN MTS DARUL ARAFAH DELI SERDANG SUMATERA UTARA - Finta Restu Darniati (UIN Sumatera Utara Medan, 2016)
The purpose of this research is: (1) to find out the results of language learning dibelajarkan students with the United Kingdom strategy Picture and Picture and language learning outcomes United Kingdom students who dibelajarkan with Cooperative Script. (2) know the United Kingdom language learning results of students who have a high degree of self-reliance and independence of students who have low. (3) find out the interaction between the learning strategies and the independence of the students against the United Kingdom language learning results. The population in this research the entire grade VII SMPS Galih Agung consists of eight classes (1a – 1 h) and grade VII MTS Darul Arafat comprising ten classes (1a – 1j). Sampling techniques in the study sample is a technique in Group lots (Cluster Random Sampling). Sample research selected classes VII-c (30 people) and VII-a (32 people) who would use the strategy of Picture and Picture on SMPS Galih Supreme and Class VII-a (30 people) and Class VII-e (34 people) to MTS Darul Arafat that will use the Script at the moment Cooperative strategy learning process takes place. An instrument for measuring the results of the research study used the test multiple choice, while shaped to get data about the independence of students used the now. Normality test with test Liliefors test test with its homogeneity while Fisher and Bartlett test. Data analysis techniques was Anava two lines on the α = 0.05 significant level followed by Scheffe test.Key words: learning strategies and independence